Policy and legal reforms for the poor in India - Saxena, N.C. (Mussoorie)
The provocation to write this booklet arose from a chance remark made by me in the first meeting of the Steering Group of the Planning Commission on "Strategies for Poverty Alleviation and Area Development in Rural India during the Ninth Plan Period", that spending millions of rupees in the name of upliftment of the poor by Government is counter productive unless the existing policies too are radically altered in favour of the poor. I gave a number of instances of anti-poor policies from the forestry sector, and Deep Joshi of PRADAN spoke in similar vein about state policies, regulations and Acts which have made the common property resources such as water bodies, stone quarries, and sand inaccessible to the poor. The Planning Commission promptly asked me to prepare a document about such policies. which could then be incorporated in the Steering Group's report.
Keywords: Poverty